Angelina Ballerina - Holabird, Katharine (Middleton, WI : Pleasant Company Publications, 2000)
Angelina loves to dance and wants to become a ballerina more than anything else in the world.
"Ages 3 and up"--Jkt.
Keywords: Mice -- Fiction; Ballet dancing -- Fiction; Dancers -- Fiction